Separate Aspects of Administrative and Legal Regulation of Activity of Passenger Taxis - Yu. V. Mishina (Сибирское юридическое обозрение, 2020)
The article discusses the features of the legal regulation of the activities for the transport of passengers and baggage by taxi in the Russian Federation in the context of ensuring road safety. The Author analyzes the specifics of participation in traffic of vehicles intended for the carriage of passengers as a passenger taxi. Attention is drawn to the formality of existing requirements for drivers applying for a permit to carry out the specified type of activity, and the need for their adjustment is justified. Suggestions are being made aimed at improving legislation in the field of taxi transportation. Separate collisions are investigated that arise in the law enforcement practice of the traffic police when exercising control and supervisory powers over the observance of road safety requirements by passenger taxis, and suggested ways to resolve them.